Hubungan antara Motivasi Belajar dan Kemampuan Analisis Fisika Siswa SMA Ditinjau dari Perspektif Gender - Nurajijah, Siti; Irvani, Asep Irvan; Muhajir, Siti Nurdianti (Mataram University, 2026)
This study focuses on evaluating the correlation between learning motivation and students’ analytical ability in physics, as well as comparing these two variables from a gender perspective. Using a quantitative approach with a correlational–comparative research design, the study involved 50 students of grade XII MIA (8 male students and 42 female students). The results indicate that: (1) there is a very strong and significant correlation between learning motivation and students’ analytical ability in physics learning (r = 0.935; Sig. 0.000 < 0.05); and (2) there is no significant difference in either analytical ability or learning motivation between male and female students. It can be concluded that learning motivation is a key factor influencing students’ success in physics analysis, regardless of gender differences.